PENGEMBANGAN MULTIMEDIA PEMBELAJARAN AKUNTANSI SEBAGAI PENUNJANG MATERI TAHAP PENCATATAN DALAM SIKLUS AKUNTANSI PERUSAHAAN JASA - Putri, Febriza Restiana; Pratiwi, Vivi (STKIP Persada Khatulistiwa Sintang, 2024)
21st century learning prepares learners to have technological skills through the provision of web-based learning multimedia. Learning multimedia that can be accessed through the website can increase motivation and make it easier for students to learn to understand the subject matter. This study aims to describe the development process, analyse the feasibility results, and determine the students' response to the wixsite-assisted accounting learning multimedia product as a support for the recording stage material in the service company accounting cycle. The subject of development research is students of class X AKL SMK PGRI 2 Sidoarjo. This research was developed with the ADDIE development model through 5 stages. The results of the development research show that learning multimedia is feasible to use with details of the results of material expert validation 91.7%, language experts 98%, and media experts 95.93%. The application of learning multimedia developed for students obtained a very good response, with a percentage result of 95%. Based on these results, wixsite-assisted accounting learning multimedia is feasible and can be used in the learning process to support the material for the recording stage of the service company accounting cycle.